SECTOR INTERCONNECTIONS AND COMPOSITION OF PRODUCT, DEMAND, AND INCOME IN MATO GROSSO DO SUL STATE’S AGRICULTURE AND LIVESTOCK FARMING: AN INPUT-OUTPUT MATRIX APPLICATION - Fagundes, Mayra Batista Bitencourt; Dias, Daniela Teixeira; Figueiredo, Adriano Marcos Rodrigues; Pitaluga, Christiane Marques (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
The aim of this article is to analyze the output, demand, income and sectoral linkages of Mato Grosso do Sul’s agriculture. A quantitative research was conducted, using an input-output matrix and GDP’s notions by the approaches of output, demand and income. Among the key findings are the concentration of purchases and sales mainly in the agriculture itself and in the food and beverage sector. About the GDP’s approaches, the agriculture has positioned itself among the top five outputs. By the income approach, agricultural taxation and wages reached small sharesof the economy. By the demand side, the highlight was the share of exports to the rest of Brazil. These results demonstrated the importance of agriculture in Mato Grosso do Sul’s economy, providing support to decision-making within this sector and the government.